2012
DOI: 10.1667/rr2859.1
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression Profiles in White Blood Cells of Volunteers Exposed to a 50 Hz Electromagnetic Field

Abstract: Consistent and independently replicated laboratory evidence to support a causative relationship between environmental exposure to extremely low-frequency electromagnetic fields (EMFs) at power line frequencies and the associated increase in risk of childhood leukemia has not been obtained. In particular, although gene expression responses have been reported in a wide variety of cells, none has emerged as robust, widely replicated effects. DNA microarrays facilitate comprehensive searches for changes in gene ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…In another study, Kirschenlohr et al showed that an extremely low-intensity EMF was also effective in expressing genes in white blood cells. 17 Moreover, according to the findings obtained by Gottwald et al, EMF is proved to be effective in the production of proteins in some cells. This factor along with other critical factors increases the growth and proliferation of cells.…”
Section: Introductionmentioning
confidence: 95%
“…In another study, Kirschenlohr et al showed that an extremely low-intensity EMF was also effective in expressing genes in white blood cells. 17 Moreover, according to the findings obtained by Gottwald et al, EMF is proved to be effective in the production of proteins in some cells. This factor along with other critical factors increases the growth and proliferation of cells.…”
Section: Introductionmentioning
confidence: 95%
“…Furthermore, we could show that LF-EMF application did not result in any gene expression changes of hMSCs during chondrogenic differentiation as examined by microarray analysis. This is of major importance as previous reports have linked EMF with an increased risk of carcinogenesis [ 16 18 ] and there is a growing concern in public health regarding EMF [ 36 ]. In this study, three weeks of LF-EMF did not cause any inadvertent gene expression changes.…”
Section: Discussionmentioning
confidence: 99%
“…Under Low frequency electromagnetic fields (LF-EMF), the chondrogenic differentiation of hMSCs in 3D culture showed a significant increase of collagen type II expression at higher cell passages, although no EMF effect was obtained under optimal differentiation conditions [ 15 ]. However, EMF have also been reported to cause adverse effects [ 16 18 ], and the level of concern about EMF in the general population is high. Among general practitioners, there is no association between correct knowledge and concern [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several research groups have investigated transcriptomic, proteomic, or metabolomic changes following exposure to ELF or RF electromagnetic fields. Earlier studies have been reviewed [63,64], and additional studies have been published recently [65,66,67,68,69,70,71,72]. There are many limitations in individual studies such as short exposure times, limited range of exposure levels, and limited number of sampling times after exposure.…”
Section: Experimental Approachesmentioning
confidence: 99%